1990
DOI: 10.1183/09031936.93.03010006
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal mucus clearance in high-frequency oscillation: effect of peak flow rate bias

Abstract: We have reported previously that high-frequency oscillation of the chest wall (HFO/CW) enhances the tracheal mucus clearance rate (TMCR) in dogs. This enhancement of TMCR may be due in part to the expiratory bias in peak flow rate (VE/VI greater than 1) that occurs during HFO/CW. We examined this factor in 8 anaesthetized, spontaneously breathing dogs by comparing TMCR during the following manoeuvers: 1) HFO/CW, applied by means of a thoracic cuff; 2) symmetric high-frequency oscillation via the airway opening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It may be assumed that the early rapid compression force is responsible for the increase in expiratory airflow and that the oscillatory component is more important in terms of altering the mucus properties. An increase in mucus transport has been linked to increased airway oscillation, which is believed to decrease the viscosity of mucus and increase the expiratory air flow (Chang et al 1988, Gross et al 1985, King et al 1990. The exact relationship between applied force and resultant flow changes will be determined by a number of factors including the timing of applied force during the respiratory cycle, age of the child and underlying pathophysiology which will need to be explored thoroughly in future clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…It may be assumed that the early rapid compression force is responsible for the increase in expiratory airflow and that the oscillatory component is more important in terms of altering the mucus properties. An increase in mucus transport has been linked to increased airway oscillation, which is believed to decrease the viscosity of mucus and increase the expiratory air flow (Chang et al 1988, Gross et al 1985, King et al 1990. The exact relationship between applied force and resultant flow changes will be determined by a number of factors including the timing of applied force during the respiratory cycle, age of the child and underlying pathophysiology which will need to be explored thoroughly in future clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…High frequency chest wall oscillation provided at the mouth by a pistol pump did not improve tracheal mucus clearance rate in mechanically ventilated dogs (King et al, 1984). However in a follow up study mucus transport rates increased by 99% (+/-11) during high frequency oscillation with an expiratory flow bias compared to control (King et al, 1990). The Metaneb is a new generation IPV device, which provides a simultaneous combination of positive pressure, continuous high frequency oscillations and aerosol delivery (Ferguson and Wright, 2017).…”
Section: Mechanical Adjunctsmentioning
confidence: 97%
“…Factors favouring two phase gas liquid flow transport in-vivo include: the inclined orientation of airway branches which may reduce the influence of gravity, and the presence of the PCL which will aid movement of the mucus layer (Kim et al, 1987, Kim et al, 1986b. Animal studies have demonstrated cephalad movement of mucus in situations with an expiratory flow bias (Benjamin et al, 1989, King et al, 1990)…”
Section: Two Phase Gas Liquid Flowmentioning
confidence: 99%
See 1 more Smart Citation